Pasteurella multocida Septicemia in a Patient with Cirrhosis: An Autopsy Report - Takuma Yamamoto; Takahiro Umehara; Takehiko Murase; Kazuya Ikematsu (Case Reports in Infectious Diseases)
More people are keeping pets in their homes but may not be sufficiently aware of the potential danger from infections. We report an autopsy case of a 57-year-old man affected by cirrhosis. Septic shock with Pasteurella multocida pneumonia was the cause of his death. P. multocida was the source of infection via the respiratory tract and caused pneumonia. Cirrhosis is one of the risk factors for P. multocida infection. A detailed patient history about animal exposure should be obtained and a differential diagnosis of P. multocida infection must be kept in mind.